Structural Modification of La2O3-TiO2-B Mixture After Mechanical Activation; IOP Conference Series: Materials Science and Engineering; Vol. 142 : Innovative Technologies in Engineering - Dolmatov O. Yu. Oleg Yurevich (2016, 2016)
Title screen